Learning of the Yellow Book at Dayah Misbahul Huda Buket Rata, Lhokseumawe City - Prayoga, Maditya (Islamic Studies in the World, 2025)
Background. YellowIslamic classic book learning at Dayah Misbahul Huda Buket Rata, Lhokseumawe, is an integral part of traditional Islamic education in Aceh. This study aims to analyze the learning traditions, teaching methods, and materials used in learning the yellowIslamic classic book, as well as its relevance in the context of modern Islamic education.. Purpose. This research aims to explore how Dayah Misbahul Huda adopts a curriculum that integrates formal education with religious learning, and applies interactive lecture and discussion methods. Method. The research method used is descriptive qualitative with in-depth interviews with santri, ustaz, and dayah leaders. Results. The results show that religious activities such as yasinan and congregational prayers are also an important part of the educational process, which strengthens the religious and cultural identity of santri. Despite being faced with the challenges of modernization, Dayah Misbahul Huda remains relevant as an authentic religious learning center, contributing to the spiritual and intellectual development of santri. Conclusion. This research confirms the importance of preserving the tradition of yellowclassic book learning in the face of the dynamics of the times and contributes to an understanding of the role of dayah in maintaining the intellectual heritage of Islam.